낙동강 상류 서식 어류의 부위별 중금속 분포 특성 - 권희원(Hee Won Kwon); 김영훈(Young Hun Kim); 김정진(Jeong Jin Kim) (자원환경지질, 2022)
Fish that inhabited in the watersheds of Andong, Imha and Yeongju Dam in the upper Nakdong River were analyzed heavy metals by separated into muscle, gill, stomach and liver part. Thirteen fish species such as dark chub, skygager, coreoperca herzi, Korean piscivorous chub, cornet fish, Japan crucian carp, catfish, bass, crucian carp, mandarin fish, carp, long-nosed barbel, Korean sharpbelly were analyzed using ICP/MS. The results of the analysis based on the overall average concentration showed that the muscle part is lower than other parts in all heavy metal items except mercury. The gill part showed high concentrations of chromium, manganese, nickel, and lead, the stomach part has high zinc, and the liver part showed high concentrations of iron, copper, arsenic, and cadmium. 낙동강 상류지역의 안동댐, 임하댐, 영주댐 유역에 서식하는 물고기에 대하여 근육부, 아가미, 위, 간 부위로 분리하여 중금속 분석을 수행하였다. 분석한 물고기는 갈겨니(dark chub), 강준치(skygager), 꺽지(coreoperca herzi), 끄리(Korean piscivorous chub), 누치(cornet fish), 떡붕어(Japan crucian carp), 메기(catfish), 배스(bass), 붕어(crucian carp), 쏘가리(mandarin fish), 잉어(carp), 참마자(long-nosed barbel), 치리(Korean sharpbelly) 등 13개 어종으로 ICP/MS를 이용하여 분석하였다. 분석 결과 전체 평균 농도를 기준으로 근육부는 수은을 제외한 모든 중금속 항목에서 다른 부위에 비해 낮았다. 아가미 부위는 크롬, 망간, 니켈, 납, 위 부위는 아연, 간 부위는 철, 구리, 비소, 카드뮴이 다른 금속에 비해 높은 농도값을 나타내었다.